2002
DOI: 10.1021/ac010837s
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Ion Mobility Separations, Collisional Activation Techniques, and Multiple Stages of MS for Analysis of Complex Peptide Mixtures

Abstract: An ion trap/ion mobility/quadrupole/collision cell/time-of-flight mass spectrometer that incorporates a differentially pumped orifice-skimmer cone region at the back of the drift tube has been developed for the analysis of peptide mixtures. The combined approach allows a variety of strategies to be employed for collisionally activating ions, and fragments can be monitored by subsequent stages of mass spectrometry in a parallel fashion, as described previously (Anal. Chem. 2000, 72, 2737). Here, we describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 44 publications
1
72
0
Order By: Relevance
“…Nested ion mobility/timeof-flight mass spectrometry measurements were carried out using a home-built instrument at Indiana University. While a number of instrumental designs have been described [37,38] (and are likely to be valuable for these types of studies), the instrument used for these studies is a low-pressure drift tube that utilizes a drift region created by a series of insulating and conducting spacers which, when compressed, make the cavity that contains the buffer gas.…”
Section: Ion Mobility Spectrometrymentioning
confidence: 99%
“…Nested ion mobility/timeof-flight mass spectrometry measurements were carried out using a home-built instrument at Indiana University. While a number of instrumental designs have been described [37,38] (and are likely to be valuable for these types of studies), the instrument used for these studies is a low-pressure drift tube that utilizes a drift region created by a series of insulating and conducting spacers which, when compressed, make the cavity that contains the buffer gas.…”
Section: Ion Mobility Spectrometrymentioning
confidence: 99%
“…IMS has now been coupled to quadrupole MS [10], time-of-flight MS [13], and FTICR [14]. The IMS/TOF hybrid that disperses analyte mixtures in mobility and mass dimensions simultaneously is a promising new platform for high-throughput analytical applications [15,16].…”
mentioning
confidence: 99%
“…Reviews of IMS methods are given elsewhere [25,[33][34][35][36] and the overall approach associated with IMS-TOF measurements has been described [37][38][39][40]. A schematic diagram of the instrument that was used in these studies is shown in Figure 1.…”
Section: Generalmentioning
confidence: 99%
“…In the latter case, fragmentation occurs on a timescale that is much shorter than residence times of ions in the first field region of the drift tube. Therefore, it is possible to correlate fragments with precursor ions because they have the same total drift times, as described previously [39]. Upon exiting the drift tube, precursor ions (or precursors and fragments) are focused into the source region of a reflectron geometry TOF mass spectrometer and dispersed again according to differences in m/z ratios.…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation